2022
DOI: 10.1002/prs.12334
|View full text |Cite
|
Sign up to set email alerts
|

Gas pipeline safety management system based on neural network

Abstract: The risk of leakage poses a grave threat to natural gas pipeline safety. The high compressibility of gases combined with unsteady boundary conditions makes detecting leaks in pipelines a challenging endeavor. To date, in the literature, only a limited number of studies have focused on leak detection and diagnostics in gas mixture pipelines. The present study provides a system for detecting, locating, and estimating the size of small gas leaks from a compressible and dynamic natural gas flow in pipelines with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The fusion of data from multiple sources can provide a more comprehensive view of the system and help assess the operational status and potential risks of pipelines more accurately [7]. An efficient, intelligent gas pipeline management system usually includes several key components, including data collection, data storage, data analysis, and decision support [8][9][10]. The system should be able to collect and process data from various sensors and databases in real-time, utilize advanced data analysis techniques (e.g., machine learning and artificial intelligence) to perform risk assessment and prediction, and provide effective decision support [11].…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of data from multiple sources can provide a more comprehensive view of the system and help assess the operational status and potential risks of pipelines more accurately [7]. An efficient, intelligent gas pipeline management system usually includes several key components, including data collection, data storage, data analysis, and decision support [8][9][10]. The system should be able to collect and process data from various sensors and databases in real-time, utilize advanced data analysis techniques (e.g., machine learning and artificial intelligence) to perform risk assessment and prediction, and provide effective decision support [11].…”
Section: Introductionmentioning
confidence: 99%
“…Preference [1][2] detects pressure changes in the pipe network using high-frequency pressure sensors, and identifies leakage conditions in the pipe network using negative pressure waves; Ahmad et al [3] used continuous wavelet transform to obtain acoustic image features from time series acoustic emission signals, and then identified the pipeline leakage state through neural network; Mujtaba et al [4] identified the fault category of specific gas pipeline through shallow neural network classifier (SNNC); Zhang Yong et al [5] optimized Elman neural network by genetic algorithm (GA) and applied it to pipeline leakage identification.…”
Section: Introductionmentioning
confidence: 99%
“…A safety management system (SMS) is an important part of every organization as its ignorance can lead to loss of lives, property, and productivity 1 . The efficient analysis of incident data helps companies pinpoint the weakness in the safety management system and it helps to plan future training and operations planning decisions 2 .…”
Section: Introductionmentioning
confidence: 99%